Replace Experimental and Numerical Study on Ocean Current Turbine Performance with Innovative Idea Using Toroidal Propeller - Dendy Satrio; Mohammad Fahrur Riza Al Azizy; Deva Ery Aditya Putra; Sandi Jagat Pasma; Dio Alif Wahyudo; Zaidan Arsa Sulthana (Department of Ocean Engineering, 2025)
According to the HEESI, the share of renewable energy production is only 13.29% of the total energy production, with a target of 23% by 2025. One promising renewable energy source with a potential of 41 GW is ocean currents. To harness this potential, propeller turbines can be used. Propellers are a critical component of these turbines, typically designed based on the Wageningen B series. However, this series still exhibits issues such as cavitation and noise during operation. Toroidal propellers offer advantages by eliminating tip vortices, resulting in quieter operation, and reduced fatigue. This study aims to enhance the efficiency of propeller turbines through modifications using toroidal propellers. The study employs ANSYS Fluent for simulation and experiments. The process includes designing toroidal propellers with a maximum diameter of 3 meters, blade pitch angles of 60°, and blade counts ranging from 3 to 9. These designs are then simulated to analyze power and efficiency. Performance testing will measure RPM, and observe cavitation. The results are for blades ranging from 3 to 9 generates 42.6 to 63.2 kW. Therefore the best design is 9 blades that generate 63.7 kW of power with a maximum RPM of 89.9.